2016
DOI: 10.3775/jie.95.930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cellulase Activity in Enzymatic Hydrolysis Residues for Efficient Enzyme Reuse

Abstract: Enzymatic hydrolysis by cellulase has potential as an environment-friendly technology for producing bioethanol from lignocelluloses, but its production cost remains expensive. Therefore, several studies have examined methods in reducing the cost of enzymatic hydrolysis, and one of the most effective ways is to reuse enzymes. In this study, we developed a method for evaluating the cellulase activity in enzymatic hydrolysis residues for efficient enzyme reuse. Approximately 70% the of cellulase activity remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This may be because of the relatively weak binding forces via non covalent bonds. Some enzyme molecules cannot be effectively absorbed onto MWCNTs (Hasegawa et al 2016). The decreased activity may also be due to the hydrophilic characteristics of sodium alginate.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of the relatively weak binding forces via non covalent bonds. Some enzyme molecules cannot be effectively absorbed onto MWCNTs (Hasegawa et al 2016). The decreased activity may also be due to the hydrophilic characteristics of sodium alginate.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulase enzyme is by far one of the most effective enzymes to be used alone in the enzymatic hydrolysis (Kim et al, 2001;Hasegawa et al, 2016). A study conducted by Hasegawa et al, (2016) suggested that recycling cellulase enzymes after each enzymatic hydrolysis could solve the problem of their high cost as it was found that approximately 70% the of cellulase activity remained in the solid residue after 70% of the glucan was hydrolyzed, and 22% of cellulase activity remained in the solid residue after 99% of glucan was hydrolyzed. Multiple studies reached the fact that glucose release is controlled by removing of xylose and hemicellulose coating on cellulose.…”
Section: The Collection Of Phb By Centrifugingmentioning
confidence: 99%